Cognitive and Socioemotional Development at 5 and 9 Years of Age of Children Born with Very Low Birth Weight and Extremely Low Birth Weight in the Czech Republic - Švandová, Lucie; Ptáček, Radek; Vňuková, Martina; Ptáčková, Hana; Anders, Martin; Bob, Petr; Weissenberger, Simon; Marková, Daniela; Sebalo, Ivan; Raboch, Jiří; Goetz, Michal (Medical science monitor, 2022)
BACKGROUND There is a high prevalence of cognitive and socioemotional dysfunction in very low birth weight (VLBW <1500 g) and extremely low birth weight (ELBW <1000 g) children. This study from the Czech Republic aimed to compare the cognitive and socioemotional development at 5 and 9 years of age of children born with VLBW/ELBW with children born with normal birth weight (NBW ≥2500 g). MATERIAL AND METHODS The clinical group consisted of 118 VLBW/ELBW children and the control group consisted of 101 children with NBW at ages 5 to 9 years. The research battery included selected subscales from the Intelligence and Development Scales (IDS), A Developmental Neuropsychological Assessment - second edition (NEPSY-II), and the Behavior Rating Inventory of Executive Function (BRIEF). Data were analyzed using STATA IC v. 15 software and G*Power (descriptive statistic, analysis of variance (ANOVA), correlations, multivariate analysis of variance - MANOVA, post hoc power analysis). RESULTS We found a statistically significant difference in cognitive and socioemotional development between children with VLBW/ELBW and those with NBW. The average intelligence quotient (IQ) of VLBW/ELBW children was 96.38, while that of NBW children was 12.98 points higher (P<0.001). NBW children achieved better results on all subtests of the IDS (P<0.001) as well as in affect recognition (P<0.001). All results for both groups were within normal range. Parents of VLBW/ELBW children did not recognize impaired executive functioning (P=0.494). CONCLUSIONS This study has shown significant cognitive and socioemotional deficit in children born with VLBW and ELBW when evaluated at 5 and 9 years of age.
Keywords: novorozenec s velmi nízkou porodní hmotností; novorozenec; Infant, Newborn; Humans; dítě; kognice; Child; porodní hmotnost; analýza rozptylu; novorozenec s extrémně nízkou porodní hmotností; Analysis of Variance; lidé; Infant, Very Low Birth Weight; předškolní dítě; Birth Weight; Czech Republic; Infant, Extremely Low Birth Weight; Česká republika; Child, Preschool; Cognition